Inactivation of Salmonella typhimurium SL1344 by Chlorogenic Acid and the Impairment of Cellular Integrity - Yang, Liang; Zhang, Chunlin; Su, Zijing; Zhao, Liang; Wu, Jiaxin; Sun, Xiaoying; Zhang, Xiujuan; Hu, Xiaoqing (Frontiers in Microbiology, 2022)
Chlorogenic acid (CGA) is an antibacterial agent that can be isolated from Eucommia ulmoides Oliver, a Chinese medicinal and edible plant food. The inhibitory effect of CGA on bacterial growth and stiffness of the outer membrane (OM) had been reported, while more evidence were required to elucidate its impairment of cell wall. In this study, the morphological and physiochemical changes of Salmonella cells under CGA treat-ment were investigated. Firstly, the minimum inhibitory concentration (MIC) of CGA against Salmonella was assayed. Later, the permeability of OM and activity of the pro-teins released were measured and observed to reveal the alteration of OM characteristic and cellular morphology. Finally, reactive oxygen species and cell membrane fluidity were analyzed respectively to elucidate how CGA damaged cell surface. The results showed that MIC of CGA against Salmonella was 6.25 mg/L. Under sub-lethal doses of CGA, the OM permeability and the release of soluble proteins were enhanced evi-dently, and Salmonella cells showed more deformed and shrunken, confirming the im-pairment of cellular integrity under CGA. Finally, the possible cause of cell surface damage was investigated. the fluidity of the membrane was increased upon CGA treat-ment, which may the possible cause of OM by CGA.